Induction of stress defense response and quality retention in minimally processed peaches through the application of gamma irradiation treatments - Colletti, Analia Cecilia; Denoya, Gabriela Inés; Budde, Claudio Olaf; Gabilondo, Julieta; Pachado, Jose Alberto; Vaudagna, Sergio Ramon; Polenta, Gustavo Alberto (Elsevier, 2022)
Consumers demand fruit and vegetable products "on the go" that maintain color, flavor, nutritional and bioactive compounds almost equal to fresh products. Irradiation represents an effective technology traditionally used in fruit and vegetable as a phytosanitary treatment to preserve food quality and safety. In the present study we evaluated the effect of gamma irradiation treatments at several doses (0, 0.1, 0.3, 1.0, 2.5 kGy) on the quality and biochemical aspects of minimally processed peaches (Prunus persica L. Batsch) with low oxygen permeability packaging. During minimal processing, peach slices were treated in an antioxidant solution containing 1 % ascorbic acid and 0.5 % citric acid for 2 min. Trays of minimally processed peaches were irradiated packed inside cardboard boxes. Changes in color, firmness and polyphenoloxidase (PPO) and peroxidase (POD) activities of peaches were analyzed at different storage times (0, 7, 14 d) at 4 °C. In addition, the stress response of plant to these treatments was assessed by using the induction of heat shock proteins (HSP) as a biochemical marker. Results show that irradiation caused no substantial changes in chromatic parameters, although an immediate reduction in firmness and POD activity was observed, proportional to the increased doses applied. In turn, PPO activity remained stable while the activity of some of its isoenzymes decreased for doses higher than 0.3 kGy. The overexpression of HSP, only detected for irradiation doses of 0.1 and 0.3 kGy, in coincidence with the best performing treatments, constitutes a relevant finding not previously reported in fruit. Therefore, low doses of irradiation promoted the physiological and biochemical defense mechanisms of the fruit. HSP could thus be used in plant tissues as a biomarker of the stress brought about by exposure to irradiation, capable of preventing physiological damage. These preliminary results suggest that irradiation treatments (up to 1.0 kGy) in combination with modified atmosphere packaging (from 19 % and 10 % O2 at 0 d to 3 % and 15 % CO2 at 14 d of storage) could render high quality peach products with an extended shelf life. // Resumen: Los consumidores exigen productos de frutas y verduras "sobre la marcha" que mantengan el color, el sabor y los compuestos nutricionales y bioactivos casi iguales a los productos frescos. La irradiación representa una tecnología eficaz utilizada tradicionalmente en frutas y hortalizas como tratamiento fitosanitario para preservar la calidad e inocuidad de los alimentos. En el presente estudio evaluamos el efecto de tratamientos de irradiación gamma a varias dosis (0, 0.1, 0.3, 1.0, 2.5 kGy) sobre la calidad y aspectos bioquímicos de duraznos (Prunus persica L. Batsch) mínimamente procesados ​​con empaques de baja permeabilidad al oxígeno. Durante el procesamiento mínimo, las rodajas de durazno se trataron en una solución antioxidante que contenía 1 % de ácido ascórbico y 0,5 % de ácido cítrico durante 2 min. Se irradiaron charolas de duraznos mínimamente procesados ​​empacados dentro de cajas de cartón. Se analizaron los cambios en el color, la firmeza y las actividades polifenoloxidasa (PPO) y peroxidasa (POD) de los duraznos a diferentes tiempos de almacenamiento (0, 7, 14 d) a 4 °C. Además, se evaluó la respuesta de estrés de la planta a estos tratamientos utilizando la inducción de proteínas de choque térmico (HSP) como marcador bioquímico. Los resultados muestran que la irradiación no provocó cambios sustanciales en los parámetros cromáticos, aunque se observó una reducción inmediata de la firmeza y de la actividad POD, proporcional al aumento de las dosis aplicadas. Por su parte, la actividad de la PPO se mantuvo estable mientras que la actividad de algunas de sus isoenzimas disminuyó para dosis superiores a 0,3 kGy. La sobreexpresión de HSP, detectada únicamente para dosis de irradiación de 0.1 y 0.3 kGy, en coincidencia con los tratamientos de mejor desempeño, constituye un hallazgo relevante no reportado previamente en fruta. Por lo tanto, bajas dosis de irradiación promovieron los mecanismos de defensa fisiológicos y bioquímicos de la fruta. Por lo tanto, la HSP podría utilizarse en tejidos vegetales como un biomarcador del estrés provocado por la exposición a la radiación, capaz de prevenir el daño fisiológico. Estos resultados preliminares sugieren que los tratamientos de irradiación (hasta 1,0 kGy) en combinación con el envasado en atmósfera modificada (desde 19 % y 10 % de O2 a los 0 días hasta 3 % y 15 % de CO2 a los 14 días de almacenamiento) podrían generar productos de durazno de alta calidad con una vida útil prolongada.